Parliament Ltd : A Journey to The Dark Heart of British Politics - Williams, Martin (London Hodder & Stoughton, 2016)
Investigative journalist Martin Williams lifts the lid on the hidden greed and corruption within British politics in this explosive expose.
Include Index
Keywords: Political corruption -- Great Britain -- Politics and government